(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe of some clinical and paraclinical characteristics of stage IV lung adenocarcinoma patients at Nam Dinh provincial General Hospital. Subjects and methods: A retrospective and prospective descriptive study was conducted on 30 patients with stage four lung adenocarcinoma at the Oncology Center of Nam Dinh provincial General Hospital from 2022 to 2025. Results: Clinical symptoms were predominantly persistent cough (53.3%), chest pain (43.3%), weight loss (33.3%), and palpable lymph nodes in the neck (20%). Imaging characteristics: primary tumor location was most commonly on the right side (70%) and peripheral (63.3%); tumor size was more common in stage T4 (93.3%) than T3 (6.7%); mediastinal lymph node metastasis accounted for 50%, and hilar lymph node metastasis accounted for 33.3%. Conclusion: The most common clinical symptoms are persistent cough and chest pain. The primary tumor is more frequently located on the left than the right, and more often peripherally than centrally; tumor size is most common at stage T4, and mediastinal lymph node metastasis is most prevalent.